Aktinische Keratosen - Heppt, Markus; Steeb, Theresa; Szeimies, R. M.; Berking, Carola (Hautarzt, 2020)
Actinic keratoses (AK) are common precancerous cutaneous lesions in fair-skinned individuals as a result of cumulative exposure to ultraviolet radiation. Due to their high prevalence, AK account for a large disease burden, in particular in older persons. As AK may potentially progress into invasive cutaneous squamous cell carcinoma, guidelines recommend early and consequent treatment. Numerous lesion- and field-directed interventions with different efficacy and safety profiles are currently licensed in Germany. The appropriate intervention should be chosen together with the patient based on his or her motivation and expectations towards the treatment.
CRIS-Team Scopus Importer:2020-06-05
Keywords: 5‑Fluorouracil; Ingenol mebutate; Non-melanoma skin cancer; Photodynamic therapy; Squamous cell carcinoma